2015
DOI: 10.1007/s00464-015-4533-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal onlay mesh reinforcement of the abdominal wall: a new surgical option for treatment of anterior cutaneous nerve entrapment syndrome—a retrospective cohort analysis of 30 consecutive patients

Abstract: Intraperitoneal onlay mesh reinforcement of the abdominal wall seems to be a promising option for the treatment of intractable anterior cutaneous nerve entrapment syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Stirler et al29 suggested that intraperitoneal onlay mesh reinforcement may prevent the entrapment of anterior cutaneous nerves of the neurovascular bundle in patients with refractory ACNES. All 40 patients who participated in the study had a prior injection of a local anesthetic combined with a corticosteroid (>2 consecutive injections at the relevant trigger point), but there was no permanent relief in 30 of them.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Stirler et al29 suggested that intraperitoneal onlay mesh reinforcement may prevent the entrapment of anterior cutaneous nerves of the neurovascular bundle in patients with refractory ACNES. All 40 patients who participated in the study had a prior injection of a local anesthetic combined with a corticosteroid (>2 consecutive injections at the relevant trigger point), but there was no permanent relief in 30 of them.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…7/10 on a numerical scale. Pain is usually described as sharp, although descriptions vary, and occurs predominantly on the right side (61%, 62%, 63%, 68%, and 74%, respectively) (4,15,19,22,23); however, many left-sided bilateral cases have been reported (12,24). The reason for the higher prevalence of right-sided ACNES than left-sided remains unclear; however, it could be inferred that it is more common on the right side because of the global prevalence of right-handed individuals and the fact that many people exert more effort on their right side.…”
Section: Study Selectionmentioning
confidence: 99%